2021
DOI: 10.1126/scitranslmed.abd9898
|View full text |Cite
|
Sign up to set email alerts
|

Integrated trajectories of the maternal metabolome, proteome, and immunome predict labor onset

Abstract: Estimating the time of delivery is of high clinical importance because pre- and postterm deviations are associated with complications for the mother and her offspring. However, current estimations are inaccurate. As pregnancy progresses toward labor, major transitions occur in fetomaternal immune, metabolic, and endocrine systems that culminate in birth. The comprehensive characterization of maternal biology that precedes labor is key to understanding these physiological transitions and identifying predictive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(122 citation statements)
references
References 91 publications
3
115
0
4
Order By: Relevance
“…New strategies should focus on better prediction of chorioamnionitis and may include the use of omics ( Ngo et al., 2018 ). Integrated trajectories of maternal metabolome, proteome, and immunome could define and characterize the patients at risk ( Pique-Regi et al., 2019 ; Stelzer et al., 2021 ). Treatment strategies may include the modulation of maternal immune responses such as the use of extracellular vesicles (exosomes) or peptides ( Spinelli et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…New strategies should focus on better prediction of chorioamnionitis and may include the use of omics ( Ngo et al., 2018 ). Integrated trajectories of maternal metabolome, proteome, and immunome could define and characterize the patients at risk ( Pique-Regi et al., 2019 ; Stelzer et al., 2021 ). Treatment strategies may include the modulation of maternal immune responses such as the use of extracellular vesicles (exosomes) or peptides ( Spinelli et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors identified a distinct molecular shift that occurred 2-4 weeks before delivery where pregnancy maintenance transitioned to pre-labor biology. The molecular shift involved metabolomic, proteomic, and immunologic systems and occurred with similar accuracy in both term and preterm women ( Stelzer et al., 2021 ).…”
Section: Birth Is An Inflammatory Eventmentioning
confidence: 95%
“…Both applying approaches developed for other conditions to sepsis and ARDS and developing novel approaches will be necessary. Potential areas for advancement include methods to identify patients who benefit by incorporating combinations of clinical and molecular markers across multiple omics platforms (combining deep phenotyping with HTE identification), as has recently been explored in other non–critical care disorders ( 40 , 41 ), to modify treatment approaches in response to the rapid changes in the host immune response over time, and to use causal modeling when RCT data are sparse and only results of observational studies are available ( 42 ) ( Table 3 ).…”
Section: Recommendationsmentioning
confidence: 99%